Comparative study of hemorrhagic and ischemic complications among anticoagulants in patients undergoing cryoballoon ablation for atrial fibrillation. Issue 1 (January 2017) - Okishige, Kaoru; Nakamura, Tomofumi; Aoyagi, Hideshi; Kawaguchi, Naohiko; Yamashita, Mitsumi; Kurabayashi, Manabu; Suzuki, Hidetoshi; Asano, Mitsutoshi; Shimura, Tsukasa; Yamauchi, Yasuteru; Sasano, Tetsuo; Hirao, Kenzo
Abstract: Objective: Few data exist to evaluate the safety and efficacy of direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) undergoing cryoballoon ablation (CB-A). This study is aimed to clarify the usefulness of DOACs in patients undergoing CB-A. Methods: The patients (average age; 65.8 ± 11.9 years old, male 69%) were stratified into one of five subsets based on the type of anticoagulation (warfarin, apixaban, dabigatran, rivaroxaban, or edoxaban), and underwent CB-A. A brain MRI was performed in all patients the day after the CB-A for AF. A total of 257 (19 on warfarin, 30 on apixaban, 66 on dabigatran, 81 on rivaroxaban, and 61 on edoxaban) patients met the inclusion criteria. Results: The incidence of silent cerebral ischemic lesion was 1 (11.1%) patients on warfarin, 5 (33.3%) on apixaban, 8 (27.6%) on dabigatran, 10 (21.3%) on rivaroxaban, and 10 (29.4%) on edoxaban ( p  = 0.17). Major ischemic events occurred in one patient (1.6%) on edoxaban and one (5.3%) on warfarin. Minor bleeding complications occurred in 1 patient (5.3%) on warfarin, 2 (6.7%) on apixaban, 1 (1.2%) on rivaroxaban, 5 (7.6%) on dabigatran, and 2 (3.3%) on edoxaban ( p  = 0.24). Of note, major bleeding complications occurred in 2 patients (3.3%) on apixaban, 1 (1.2%) on rivaroxaban, 1 (1.5%) on dabigatran, 1 (1.6%) on edoxaban, and 2 (10.5%) on warfarin ( p  < 0.05). Conclusions: Warfarin use significantly increased the risk of serious bleeding, in contrast, CB-A did not place the patients at an increased risk of complications under a DOAC treatment. There were no significant differences regarding preventing embolic events among the DOAC drugs.